The Evolution of Genomic Instability in the Obligate Endosymbionts of Whiteflies - Sloan, Daniel B. (Oxford University Press, 2013)
Many insects depend on ancient associations with intracellular bacteria to perform essential metabolic functions. These endosymbionts exhibit striking examples of convergence in genome architecture, including a high degree of structural stability that is not typical of their free-living counterparts. However, the recently sequenced genome of the obligate whitefly endosymbiont Portiera revealed features that distinguish it from other ancient insect associates, such as a low gene density and the presence of perfectly duplicated sequences. Here, we report the comparative analysis of Portiera genome sequences both within and between host species. In one whitefly lineage (Bemisia tabaci), we identify large-scale structural polymorphisms in the Portiera genome that exist even within individual insects. This variation is likely mediated by recombination across identical repeats that are maintained by gene conversion. The complete Portiera genome sequence from a distantly related whitefly host (Trialeurodes vaporarium) confirms a history of extensive genome rearrangement in this ancient endosymbiont. Using gene-order-based phylogenetic analysis, we show that the majority of rearrangements have occurred in the B. tabaci lineage, coinciding with an increase in the rate of nucleotide substitutions, a proliferation of short tandem repeats (microsatellites) in intergenic regions, and the loss of many widely conserved genes involved in DNA replication, recombination, and repair. These results indicate that the loss of recombinational machinery is unlikely to be the cause of the extreme structural conservation that is generally observed in obligate endosymbiont genomes and that large, repetitive intergenic regions are an important substrate for genomic rearrangements.